Use of Abbreviations, Acronyms, and Mixed Indonesian Language Codes On Social Media - Prakoso, Ahmad Latief Devid; Kusyasi, Ahmad Najmal; Rumapea, Angela Mericia Romaulina; Sihombing, Dian Daniel Castro; Purba, George Felix; Putri, Tyara Alini; Pulungan, Hendra Kurnia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the rapidly growing use of abbreviations, acronyms, and code-mixing in Indonesian on social media. This phenomenon reflects the linguistic creativity of the younger generation, but also poses challenges to the preservation of good and correct Indonesian. This study aims to describe popular forms of abbreviations, acronyms, and code-mixing, analyze their impact on community language patterns, and provide recommendations regarding the wise use of Indonesian in the digital space. This research method is descriptive qualitative with a literature review of various related studies. The results show that abbreviations, acronyms, and code-mixing are not only forms of language efficiency but also symbols of identity, creativity, and social expression. However, excessive use can potentially reduce awareness of standard language. Therefore, education and collective awareness are needed to maintain the function of Indonesian in the digital era.